Vegetation structure and carbon stock of restored mangrove on abandoned shrimp pond in the International Mangrove Botanical Garden Rama IX, Thailand - JETSADA WONGPROM; SUTIDA MANEEANAKEKUL; ANUCHA TARA; WASAN CHANDAENG; DECHA DUANGNAMON; APISADA RUEANGKET; DUSIT WECHAKIT; POONSRI WANTHONGCHAI; CHATREE MAKNUAL (Society for Indonesian Biodiversity, 2023)
Abstract. Wongprom J, Maneeanakekul S, Tara A, Chandaeng W, Duangnamon D, Rueangket A, Wechakit D, Wanthongchai P, Maknual C. 2023. Vegetation structure and carbon stock of restored mangrove on abandoned shrimp pond in the International Mangrove Botanical Garden Rama IX, Thailand. Biodiversitas 24: 5821-5830. The conversion of mangrove forest into shrimp aquaculture has severely impacted biodiversity and increased carbon emissions. Restoration program is thus urgently needed for such mangrove forests. In this study, we investigated the vegetation structure and composition, and biomass and carbon stock of restored mangrove on abandoned shrimp pond. Observation plots at restoration sites with age of 3-year-old (MF3) and 14-year-old (MF14) were established in the International Mangrove Botanical Garden Rama IX, Chanthaburi Province, Thailand and at abandoned shrimp pond (ASP) and protected mangrove forest (PMF) as reference sites. The diameters and heights of mangrove species were measured and identified in order to determine the vegetation structure, composition, biomass, and carbon stock. Soil samples from four soil depths, i.e. 0-15, 15-30, 30-50, and 50-100 cm, were collected to quantify the soil carbon stock. The results showed the good growth of Rhizophora stand planted at the restored sites with high vegetation biomass and carbon stock. This species also promoted species diversity, suggesting that Rhizophora spp. are suitable species for the restoration of abandoned shrimp pond. The vegetation biomass and carbon stock of MF14 (230.99 t ha-1 and 102.54 t C ha-1, respectively) was higher than that of PMF (133.84 t ha-1 and 64.94 t C ha-1, respectively). Higher vegetation and soil carbon stocks of the restored mangrove forest was positively influenced by the Rhizophora stand. However, the ecosystem carbon pool of PMF was higher (366.38 t C ha-1). This result indicates that the conservation of mangrove forest is significant to maintain the forest diversity, ecosystem function, and reducing carbon emissions, while mangrove forest restoration is essential to improve the vegetation structure and increase the soil and vegetation carbon stocks.